Documentary sources on Navarre in the Section of Diversos y Códices of the National Historical Archive - Bravo Lledó, Pilar (Huarte de San Juan. Geografía e Historia, 2010)
This article covers the history of the Diversos y Códices Sections of the National Historical Archive from its foundation in 1866 to the present day. The author identifies the more interesting collections and their current organisation, both as available for reference online (PARES) and through other inventories. It focuses its interest on those archives and collections with documentation concerning Navarre, such as the Carlist archive, the Mesta archive and the War Depository, the documentary catalogues of María Cristina de Borbón, Countess of Espoz y Mina, Baldomero Espartero, Antonio Cánovas del Castillo, José Lázaro Galdiano and Federico Botella, and the decontextualised documents in the Collections. It also reports on the manuscripts that refer to Navarre in the Códices y Cartularios Section.